Breakfast skipping and cardiometabolic risk factors in adolescents: Systematic review - Souza, Marielly Rodrigues; Neves, Morgana Egle Alves; Gorgulho, Bartira Mendes; Souza, Amanda Moura; Nogueira, Patrícia Simone; Ferreira, Márcia Gonçalves; Rodrigues, Paulo Rogério Melo (Revista de Saúde Pública, 2021)
OBJECTIVE To systematically review the results of the association between breakfast skipping and cardiometabolic risk factors in adolescents. METHODS The articles were searched in May 2020 from PubMed, Virtual Health Library, Scopus, Web of Science and Scientific Electronic Library Online (SciELO). The review included observational studies conducted with adolescents (10–19 years old), which estimated the association of breakfast skipping with at least one outcome (markers of body adiposity, blood pressure, serum lipid and glucose levels). Regarding the risk of bias, the articles were evaluated using the Research Triangle Institute (RTI) Item Bank on bias risk and accuracy of observational studies. The quality of the evidence was assessed by the Grade rating. RESULTS A total of 43 articles involving 192,262 participants met the inclusion criteria and were considered in this review. The prevalence of breakfast skipping ranged from 0.7% to 94% and 60.5% of studies were classified with low risk of bias. The significant association between breakfast skipping and cardiometabolic risk factors was found in twenty-nine cross-sectional articles (n = 106,031) and four longitudinal articles (n = 5,162) for excess adiposity, in three articles (n = 8,511) for high total cholesterol levels, low-density lipoprotein and triglycerides, and in three studies (n = 6,303) for high blood pressure levels. However, there was no significant association between breakfast skipping and glycemic profile. According to the Grade rating, all the associations had low quality of evidence. CONCLUSION The results of this review suggest that breakfast skipping is associated with cardiometabolic risk factors in adolescents aged 10 to 19 years. However, considering the low quality of the evidence, the present results should be interpreted carefully. In addition, our findings highlight the importance of standardizing the definition of breakfast skipping and that more prospective studies are needed to determine how skipping breakfast can affect cardiometabolic risk factors in the long time.